2017
DOI: 10.1113/jp275084
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of fetal behavioural states during maternal sleep in healthy late gestation pregnancy: an observational study

Abstract: Fetal behavioural states (FBS) are measures of fetal wellbeing. Maternal position affects FBS with supine position being associated with an increased likelihood of fetal quiescence consistent with the human fetus adapting to a lower oxygen consuming state. Several studies have now confirmed the association between sleep position and risk of late intrauterine death. We designed this study to observe the effects of maternal sleep positions overnight in healthy late gestation pregnancy. Twenty-nine healthy women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
3
24
1
Order By: Relevance
“…With regard to withinsubjects analyses, marginal differences were found in RMSSD by state, with lower values for 1F than 2F. However, these findings follow a similar pattern of other research that used overnight recordings and found RMSSD to be lower in 1F when compared to 2F (Stone et al, 2017). Our results suggest that differences in RMSSD as a function of state should be examined as an individual characteristic.…”
Section: Discussionsupporting
confidence: 86%
“…With regard to withinsubjects analyses, marginal differences were found in RMSSD by state, with lower values for 1F than 2F. However, these findings follow a similar pattern of other research that used overnight recordings and found RMSSD to be lower in 1F when compared to 2F (Stone et al, 2017). Our results suggest that differences in RMSSD as a function of state should be examined as an individual characteristic.…”
Section: Discussionsupporting
confidence: 86%
“…24 No effect of maternal position on FHR was reported in a study by Ibrahim et al 21 as well as in the home. 25 These investigators reported that, compared with the left side, FHR during supine position was slightly increased, and that both right and supine were associated with reduced SDNN, whereas only supine was associated with decreased RMSSD. 22,25 The present study did have some limitations, including the identification of position using the Embletta system rather than with video monitoring.…”
Section: Discussionmentioning
confidence: 98%
“…25 These investigators reported that, compared with the left side, FHR during supine position was slightly increased, and that both right and supine were associated with reduced SDNN, whereas only supine was associated with decreased RMSSD. 22,25 The present study did have some limitations, including the identification of position using the Embletta system rather than with video monitoring. This choice was made in the interest of minimizing invasiveness with respect to privacy concerns and participant comfort.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study showed that maternal sleeping position can also alter the behavioural sleep states of late gestation fetuses, as determined by fetal heart rate variability (Stone et al . ). This study demonstrated that, compared to 2F, 4F activity was seen almost exclusively when the mother was in a left or right lateral position, while 1F was more common when the mother was supine (Stone et al .…”
Section: Introductionmentioning
confidence: 97%
“…This study demonstrated that, compared to 2F, 4F activity was seen almost exclusively when the mother was in a left or right lateral position, while 1F was more common when the mother was supine (Stone et al . ). Further, 4F was more common between 21.00 and 01.00 h than between 01.00 and 07.00 h (Stone et al .…”
Section: Introductionmentioning
confidence: 97%